Parenting Styles and Parent–Adolescent Relationships: The Mediating Roles of Behavioral Autonomy and Parental Authority - Bi, Xinwen; Yang, Yiqun; Li, Hailei; Wang, Meiping; Zhang, Wenxin; Deater-Deckard, Kirby (Frontiers in Psychology, 2018)
The parent-adolescent relationship has been a classic research topic, and researchers have found that parenting styles (e.g., authoritative, authoritarian) are closely related to various qualities of parent-adolescent relationships (e.g., cohesion, conflict). However, little empirical work has addressed how these variables correlate with each other in mainland China, nor has prior research addressed internal psychological mechanisms. The present study investigated the associations between parenting styles and parent-adolescent relationship factors, examined the mediating effects of adolescents’ expectations of behavioral autonomy and beliefs about parental authority, and explored whether adolescent gender moderated these effects. Results from a sample of 633 Chinese adolescents (7th grade: Mage = 13.50 ± 0.62 years, 9th grade: Mage = 15.45 ± 0.67 years, 11th grade: Mage = 17.30 ± 0.75 years) suggested similar levels of parent-adolescent conflict frequency for all parenting styles. However, for parent-adolescent conflict intensity, youth of neglectful and authoritarian parents reported higher levels compared to those with indulgent parents. The highest levels of cohesion with both parents were reported by adolescents with authoritative parents, followed by indulgent, authoritarian and neglect parenting styles. Cohesion with mothers for youth with authoritative or indulgent mothers was higher for girls than boys. Adolescents’ expectation for behavioral autonomy mediated the links between parenting style and conflict, whereas adolescents’ beliefs about the legitimacy of parental authority mediated the links between parenting style and cohesion; some of these mediating effects differed by gender. Findings highlight the importance of studying potential effects of adolescents’ values and attitudes within the family system in specific cultural contexts.